Summary proceedings of the forty-third annual meeting of the Board of Governors : September 27 - 29, 1988 - International Monetary Fund (Washington D.C. IMF, 1988)
These summary of proceedings include statements, or portions of statements, relating to the work of the fund presented by Governors during the meetings, resolutions adopted by the Board of Governors of the board over the year, reports, recommendations, so communiques issued by the committees of the Board of Governors at the time of meetings and other documents relating to the meeting
29/10/2019
Loans
Keywords: IMF; Summary proceedings